1975
DOI: 10.1093/infdis/132.5.568
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Serial Virologic and Serologic Studies of Symptomatic and Subclinical Congenitally and Natally Acquired Cytomegalovirus Infections

Abstract: Infants with congenitally (38) and natally (17) acquired cytomegalovirus infection were prospectively studied by means of virologic and multiple serologic assays. These infections were characterized by chronic viral excretion (measured in years). The quantity of virus excreted in the urine during early infancy was significantly greater in infants who acquired infection in utero, particularly amon those born with overt disease; thereafter, all three groups (congenital symptomatic, congenital asymptomatic, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0
9

Year Published

1977
1977
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(108 citation statements)
references
References 19 publications
5
94
0
9
Order By: Relevance
“…Disease correlates with high viral titres (Stagno et al 1975). No clear dissociation has been shown between damage to the ear or brain and it must remain likely that both organs can be affected by virus lysis although immunopathological processes can also be implicated (Griffiths et al 1982).…”
Section: Microcephalymentioning
confidence: 99%
See 1 more Smart Citation
“…Disease correlates with high viral titres (Stagno et al 1975). No clear dissociation has been shown between damage to the ear or brain and it must remain likely that both organs can be affected by virus lysis although immunopathological processes can also be implicated (Griffiths et al 1982).…”
Section: Microcephalymentioning
confidence: 99%
“…It may be unilateral or bilateral and may be profound (Hanshaw, Dudgeon & Marshall, 1985;Pass et al 1980). Children with high CMV titres in the urine are at increased risk of hearing loss (Stagno et al 1975) but immunopathological processes may also be involved (Griffiths et al 1982).…”
Section: Hearing Lossmentioning
confidence: 99%
“…18 In other patient populations at risk of HCMV disease, quantification of HCMV load has provided another risk factor for HCMV disease. Specifically, cross-sectional and longitudinal studies have indicated the importance of monitoring HCMV load in congenitally infected infants, 19 renal transplant recipients [20][21][22] and HIV infected patients. 23,24 There is, however, a paucity of information on longitudinal fluctuations in cytomegalovirus load in the bone marrow transplant patient.…”
mentioning
confidence: 99%
“…Возможная зависимость между цитомегаловирус-ассоциированным заболе-ванием и вирусной нагрузкой описана еще в 1975 г. в работах S. Stagno и соавт., использовавших куль-туру клеток [28]. Эти данные были впоследствии подтверждены S.Walter и соавт.…”
Section: обзоры литературыunclassified